2010
DOI: 10.12927/hcpol.2010.21901
|View full text |Cite
|
Sign up to set email alerts
|

Age Difference Explains Gender Difference in Cardiac Intervention Rates After Acute Myocardial Infarction

Abstract: many investigators have reported higher rates of cardiac procedures for males than females after acute myocardial infarction (AmI), suggesting that men are treated more aggressively than women. However, others have reported no significant differences after controlling for age, resulting in uncertainty about the existence of a true gender bias in cardiac care. In this study, a population-based cohort approach was used to calculate age-specific procedure rates by sex from administrative data. Chi-square tests an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
(103 reference statements)
1
10
0
Order By: Relevance
“…23,37,38 However, more recent studies have indicated that these sex and SES-related disparities are mostly accounted for by age and important clinical comorbidities and might be improving over time. 11,25,39,40 Similar to other studies, we found that on average women receive cardiac catheterization less often than men but that there were no significant differences between women and men in either short or long-term adjusted mortality.…”
Section: Discussionsupporting
confidence: 88%
“…23,37,38 However, more recent studies have indicated that these sex and SES-related disparities are mostly accounted for by age and important clinical comorbidities and might be improving over time. 11,25,39,40 Similar to other studies, we found that on average women receive cardiac catheterization less often than men but that there were no significant differences between women and men in either short or long-term adjusted mortality.…”
Section: Discussionsupporting
confidence: 88%
“…As an example of the former, Fransoo et al . showed that higher rates of cardiac catheterization among men are largely explained by their higher rates of heart attack, [40] consistent with the known higher rate of cardiovascular disease known in men [41]. Indeed, in a preliminary analysis we found that men were much more likely than women to be admitted to an ICU in Manitoba with a cardiovascular primary diagnosis (58.8 vs. 48.0%, P <0.0001; in Additional file 1: Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that the clinical management of men and women after AMI was very similar (22) , but other studies have shown prominent differences (16) . In setting of hospitalization for CAD, women were found to have a higher incidence of CAD risk factors like diabetes and systemic hypertension, were less likely to be smokers (14) but they presented more frequently with heart failure due to diastolic dysfunction which may explain their higher unadjusted in-hospital mortality rates in AMI (15, 16 & 17) .…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have reported higher rates of coronary interventions for males when compared to females after AMI that may indicate more aggressive management for males (14) . However, others have reported no significant gender differences, whether the MI alert was initiated in the ED or in the prehospital field, after controlling for age, resulting in uncertainty about the existence of a true gender bias in cardiac care (22) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation